Utilization of Cirebon Mask Dance Art and Culture in Learning for Elementary School Students in Cirebon City - Sukma Hadi Wiyanto; Jafar Sidik (Journal of Asian Primary Education (JoAPE), 2026)
Traditional art is an important part of national identity, yet the Cirebon Mask Dance faced declining interest among the younger generation. This study aimed to examine how the utilization of the Cirebon Mask Dance in arts and culture learning increased elementary school students' appreciation of traditional art, and to identify the benefits and challenges of integrating it into the formal curriculum. The study employed a qualitative approach with a case study design at a primary school in Cirebon City. Data were collected through semi-structured interviews with two key informants, an extracurricular coordinator teacher and an arts teacher who was also a dance practitioner, together with classroom observation and documentation, then analyzed thematically and validated through source triangulation, method triangulation, and member checking. The results show that experiential, multisensory learning of the dance increases students' enthusiasm, courage to perform, communication skills, and pride in local culture. The five mask characters convey moral values that support character education, and the dance is integrated across subjects such as fine arts, civics, and Islamic education. The main challenges are limited teacher mastery of the dance, inadequate facilities, a dense curriculum, and gender perceptions among boys. The study concludes that the Cirebon Mask Dance is an effective and meaningful medium for cultural preservation and character building at the primary education level, and recommends its wider adoption across elementary schools in the Cirebon region.